Ten-year follow-up of implantable cardioverter-defibrillator device implantation in non-ischaemic cardiomyopathy – an insight from real world practice in a large district general hospital. (14th October 2021) - Abramik, J; Moore, H.L; Doolub, G; Dayer, M.J; Furniss, G
Abstract: Introduction: The benefits of implantable cardioverter-defibrillators (ICDs) in ischaemic cardiomyopathy are well established. The DANISH study, a large randomized controlled trial of prophylactic ICD implantation, found no benefit in preventing all-cause mortality in patients with non-ischaemic cardiomyopathy (NICM). However, ESC guidelines recommend ICDs for patients with NICM and LVEF ≤35% who receive optimal medical therapy (IB recommendation). The 2014 NICE guidelines have similar endorsements but prior to that ICDs were not routinely recommended in NICM in the UK. Purpose: We evaluated clinical outcomes of patients who had ICDs implanted prior to 2014 in a NICM population at a large district general hospital. Methods: An ICD database of 454 patients at our district general hospital was retrospectively reviewed. We identified 70 patients who had ICD insertion for non-ischaemic cardiomyopathy between 2006 and 2014. Mean follow up time was 9 years 9 months (SD 23 months). 39 patients had an ICD inserted for primary prevention and 31 for secondary prevention. Data was collected from patients' electronic notes and analysed with relation to baseline demographics, mortality, complications and both appropriate and inappropriate therapy in these two subgroups. Results: The baseline patient characteristics are presented in Table 1 and show similar characteristics between the primary and secondary prevention groups, except for a higher level of CRT-D implantation in the primary prevention group (p=0.006). Table 2 shows therapy that the device delivered and complication rates. Overall, 16% of patients with an ICD for non-ischaemic cardiomyopathy received a shock for VF. 41% of patients received appropriate therapy (Shocks or Anti-Tachycardia Pacing (ATP)) from their ICD with median time to first therapy of 30 months (IQR 12–66). Shocks for VF were similar in each group (15% vs. 16%, p=0.919). Six patients (8.6%) had inappropriate shocks and two inappropriate ATP (2.9%). 9 (13%) of patients had a complication either at implant or during follow-up; two had pericardial effusions following implant of which one required pericardiocentesis, three required lead replacement due to lead failure, two developed device infections, one was anticoagulated for a lead thrombus and one patient's device failed to treat VF. Conclusion: 16% of non-ischaemic cardiomyopathy patients received a shock for VF and 41% received ICD therapy for VT or VF over a mean follow-up period of almost 10 years. This was seen in both primary and secondary prevention. Inappropriate shocks and life-threatening complications were uncommon. Funding Acknowledgement: Type of funding sources: None.